Variasi Volume Eceng Gondok Serat Komposit Dalam Peredam Suara - Razul Harfi; Gustria Alifia Achmad; Muhammad Firdausi; Sumiyanto Sumiyanto; Ucok Mulyo Sugeng (Institut Sains dan Teknologi Nasional, 2023)
ABSTRACT The development of industrial technology is very rapid. This often also causes room noise to increase. For that we need a system for sound isolation or absorption using soundproof material. Noise pollution in the form of noise can interfere with and damage hearing and is a serious threat to the quality of environmental comfort. To solve this problem, various types of sound-absorbing materials have been developed. The quality of the sound-absorbing material is indicated by the value of (coefficient of absorption of the material to sound), the greater , the better it is used as a sound absorber. The purpose of this study was to determine the volume variation of the water hyacinth stem fiber composite to the amount of sound attenuation and to determine the bond structure between the matrix components and the composite filler. The research method uses polyester resin R-108, with a catalyst material of 2%, composite fibers arranged in a woven roving from water hyacinth stems in the form of molds with 5% alkaline solution (NaOH) for 2 hours at each volume variation of 20%, 30%. and 40%. Tests Sound attenuation test and SEM test were conducted to determine the bond structure between fiber as a filler and Polyester Resin as a binder (matrix). The result of the research is that the composite material meets the absorbent with a value of greater than 0.2. The maximum Noice Absorption Coefficient (NAC) value is 0.343 at 40% filler volume with a frequency of 140 Hz. The bond matrix looks quite good against the filler. Keywords: Water Hyacinth, NaOH, Resin, Damping, SEM